Real-world outcomes of diffuse large B-cell lymphoma in the biosimilar era - Nair, Reena; Bhat, Gull Mohammad; Agrawal, Narendra; Sengar, Manju; Malhotra, Pankaj; Nityanand, Soniya; Lele, Chitra; Reddy, Pramod; Kankanwadi, Suresh; Maharaj, Narendra (Frontiers in Oncology, 2023)
Background Diffuse large B-cell lymphoma (DLBCL) is an aggressive and the most common type of non-Hodgkin lymphoma (NHL). The clinical use of rituximab has improved the treatment response and survival of patients with DLBCL. The introduction of rituximab biosimilar into healthcare system has helped in providing a cost-effective treatment to B-cell lymphoid malignancies as standard of care and has improved access to patients worldwide. The aim of this study was to observe the real-world effectiveness and safety of Reditux™ and Ristova® in DLBCL patients. Methods Observational study in adults with DLBCL receiving Reditux™ or Ristova® across 29 centers in India (2015–2022). Effectiveness and safety were assessed up to 2 years after first dose. Results Out of 1,365 patients considered for analysis, 1,250 (91.6%) were treated with Reditux™ and 115 (8.42%) with Ristova®. At 2 years, progression-free survival (PFS) 69% [hazard ratio (HR), 1.16; 95% CI, 0.80–1.67], overall survival (OS) 78.7% (HR, 1.20; 95% CI, 0.78–1.86), response rates, quality of life (QoL), and overall safety in both the cohorts were comparable. The best overall response rate (BORR) at 6 months was comparable with no statistically significant differences between the Reditux™ and the Ristova® cohorts (89.2% vs. 94.3%). In multivariate analysis, BCL-2 and VAS were significant prognostic factors for PFS. Conclusion Reditux™ and Ristova® were comparable in real-world setting. Clinical Trial Registration ISRCTN registry, identifier (ISRCTN13301166)